2017
DOI: 10.1021/acs.langmuir.7b00185
|View full text |Cite
|
Sign up to set email alerts
|

Polyanionic Antimicrobial Membranes: An Experimental and Theoretical Study

Abstract: Polycationic polymers have been widely used as antimicrobial materials because of their broad spectrum activity and potential use as new antibiotics. Herein, we report the synthesis of polyanionic antimicrobial membranes by in situ photo-cross-linking of a sulfate based anionic monomer, followed by cation-exchange with organic (quaternary ammonium or imidazolium) or metal (Ag, Cu, Fe, Zn, Na, K) cations. The resultant polyanionic membranes show high and broad spectrum antibacterial activities against both bact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 59 publications
(81 reference statements)
0
32
0
Order By: Relevance
“…These results confirmed that GO/MXene can greatly improve the tensile strength and elongation at break of PHBV. E. coli and S. aureus bacteria are generally used to detect antibacterial activity against gram-negative and gram-positive bacteria [4,75,77,78]. The antimicrobial activity against E. coli and S. aureus bacteria of the PHBV and PHBV-GO/MXene composite membranes was detected.…”
Section: Mechanical Property Antibacterial Activity and Platelet Adsorptionmentioning
confidence: 99%
“…These results confirmed that GO/MXene can greatly improve the tensile strength and elongation at break of PHBV. E. coli and S. aureus bacteria are generally used to detect antibacterial activity against gram-negative and gram-positive bacteria [4,75,77,78]. The antimicrobial activity against E. coli and S. aureus bacteria of the PHBV and PHBV-GO/MXene composite membranes was detected.…”
Section: Mechanical Property Antibacterial Activity and Platelet Adsorptionmentioning
confidence: 99%
“…Potassium (K + ) acts as counterion for the two tested anionic representatives poly(MAE‐SO 3 ) and poly(AE‐SO 3 ). Previous studies have shown that polyanionic membranes containing K + as a counterion showed no antibacterial activity 59 . In addition to the influence of the already described cationic component of the hydrogel and the permeability of the microbial membrane, the antibacterial activity also depends on the porosity of the hydrogel and the amphiphilicity of the polymer 5 .…”
Section: Resultsmentioning
confidence: 98%
“…Previous studies have shown that polyanionic membranes containing K + as a counterion showed no antibacterial activity. 59 In addition to the influence of the already described cationic component of the hydrogel and the permeability of the microbial membrane, the antibacterial activity also depends on the porosity of the hydrogel and the amphiphilicity of the polymer. 5 It appears that an interaction of all these components had a negative effect on the antibacterial activity.…”
Section: Killing Assay Using Different Hydrogelsmentioning
confidence: 99%
“…Instead, Guo et al. [ 42 ] use such groups for metal‐cation binding purposes only. Early studies by Feltz and Regelson [ 43 ] confirm an interest in ethylene/maleic anhydride copolymers as antiviral materials, but their results involving the Echo 9 virus on just the copolymer indicate little, if any, antiviral activity.…”
Section: Resultsmentioning
confidence: 99%